Behavioural effects of methylphenidate in the spontaneously hypertensive rat model of attention-deficit/hyperactivity disorder: a systematic review and meta-analysis protocol. Issue 1 (19th October 2018) - Leffa, Douglas Teixeira; Castro Panzenhagen, Alana; Luiz Rovaris, Diego; Henrique Dotto Bau, Claiton; Rohde, Luis Augusto; Horacio Grevet, Eugenio; Pires, Gabriel Natan
Abstract : Introduction: Attention-deficit/hyperactivity disorder (ADHD) is a prevalent condition related to several negative outcomes, and its pathophysiology is still poorly understood. The spontaneously hypertensive rats (SHRs) are the most commonly used animal model of ADHD. How ever, its validity, and especially its predictive validity, has been questioned. Therefore, the current protocol discloses the background, aims and methods of a systematic review and meta-analysis of studies reporting the behavioural effects of methylphenidate (MPH), the most commonly prescribed treatment for ADHD, in the SHR. Search strategy: Studies will be identified through a literature search using three different electronic databases: Medline, Embase and Web of Science. There will be no language restrictions. All s tudies that administered MPH to SHR and evaluated locomotion, attention, impulsivity or memory will be included. Screening and annotation: Studies will be prescreened based on title and abstract, and a full-text review will be performed if necessary. Screening will be performed by two authors, and any disagreement will be discussed with a third author. Data management and reporting: Data extraction will be performed by two independent authors according to a standardised form. Studies will be grouped according to the behavioural outcomes reported, and a meta-analysis will be performed for each group. The influence of predefined covariates on the effects of MPH will be evaluated using meta-regression and sensitivity analyses. Data will be reported following PRISMA guidelines.